Land Rental Markets and Household Farms in Transition: Theory and Evidence from Hungary - Johan F. M. Swinnen; Liesbet Vranken (Katholieke Universiteit Leuven, LICOS Centre for Transition Economics, 2003)
This paper analyses the detfirminants of household firms?participation in land rental markets in transition countries and what affects their access to land through rental markets. We derive several theoretical hypotheses on the impact of households?management ability, land endowment, land quality and prices, transaction costs in the land market, rural credit and labour market constraints. We test the hypotheses combining a representative dataset on land rental activities of more than 1,400 Hungarian household firms with data from the Hungarian Central Statistical Office. We find that land rental markets reallocate land to households with better firm management capacities and less endowed with land. Households combine buying and renting of land to extend their firms. The continued domination of large firm organizations in some regions restricts household's access to land. Rural credit and labour market imperfections have an important impact on land rental markets.
Keywords: Q12; Q15; D10; P23; 330; Landwirtschaftliche Pacht; Landwirtschaft; Betriebsgröße; Übergangswirtschaft; Theorie; Ungarn; Markteffizienz